2003
DOI: 10.1091/mbc.e02-08-0467
|View full text |Cite
|
Sign up to set email alerts
|

The Secretory Apparatus of an Ancient Eukaryote: Protein Sorting to Separate Export Pathways Occurs Before Formation of Transient Golgi-like Compartments

Abstract: Transmission of the protozoan parasite Giardia intestinalis to vertebrate hosts presupposes the encapsulation of trophozoites into an environmentally resistant and infectious cyst form. We have previously shown that cyst wall proteins were faithfully sorted to large encystation-specific vesicles (ESVs), despite the absence of a recognizable Golgi apparatus. Here, we demonstrate that sorting to a second constitutively active pathway transporting variant-specific surface proteins (VSPs) to the surface depended o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
111
4

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(120 citation statements)
references
References 30 publications
5
111
4
Order By: Relevance
“…The exact mechanism of this export is still elusive, however. The available data support two nonmutually exclusive models for ESV genesis: (i) lateral segregation and concentration of cyst wall material in specialized ER subcompartments (10), and/or (ii) export of cyst wall material in COPIIcoated transport vesicles that give rise to ESVs by homotypic fusion (17). In any case, analogous to the generation of vesicular tubular clusters and cis-Golgi compartments, formation of ESVs seems to require the small GTPase Sar1p 3 and thus represents a unique form of Golgi neogenesis.…”
mentioning
confidence: 66%
See 2 more Smart Citations
“…The exact mechanism of this export is still elusive, however. The available data support two nonmutually exclusive models for ESV genesis: (i) lateral segregation and concentration of cyst wall material in specialized ER subcompartments (10), and/or (ii) export of cyst wall material in COPIIcoated transport vesicles that give rise to ESVs by homotypic fusion (17). In any case, analogous to the generation of vesicular tubular clusters and cis-Golgi compartments, formation of ESVs seems to require the small GTPase Sar1p 3 and thus represents a unique form of Golgi neogenesis.…”
mentioning
confidence: 66%
“…In particular, the formation and reshuffling of intra-and intermolecular disulfide bonds is essential for establishing a cyst wall, because treatment with dithiothreitol (DTT) reversibly abolished cyst wall formation and appeared to dissolve ESVs (21). Interestingly, like conventional Golgi cisternae, ESVs are sensitive to brefeldin A and associate with two Golgi markers, ␤ЈCOPI and GiYip1 (4,17). This is strong evidence for their Golgi-like nature despite the unusual morphology.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Analysis of GlCHC expression showed that clathrin is expressed almost equally in both stages of the parasite and is located in close association with the PVs in trophozoites, and in the ESVs in immature cysts (Marti et al, 2003a;Marti et al, 2003b;Hehl and Marti, 2004;Gaechter et al, 2008). On the basis of these observations, it was suggested that recruitment of clathrin to late ESVs could serve to disperse large ESVs into smaller transport vesicles in response to the secretion signal (see below).…”
Section: Clathrinmentioning
confidence: 99%
“…The fact that both constitutive and regulated mechanisms for protein transport exist in Giardia is an example of Golgi functions, since the sorting and selection process generally occurs in the trans-Golgi network in more complex cells (Gu et al, 2001). The constitutive pathway in Giardia is represented by continuous expression and trafficking to the plasma membrane of the transmembrane-anchored variant-specific surface proteins (VSPs) (Nash, 2002;Marti et al, 2003a;Touz et al, 2005). The regulated pathway takes place only during encystation and associates with the appearance of encystation-specific vesicles (ESVs), which transport cyst wall components to the plasma membrane of the encysting cell and release their content to the cell exterior during cyst wall formation (Reiner et al, 1989;McCaffery and Gillin, 1994;Lujan et al, 1995;Sun et al, 2003).…”
Section: Giardia Secretory Pathwaymentioning
confidence: 99%